Investigating Report Cards to Predict the Academic Performance of New MBA Students - Mishra, Amitabh; Agrawal, Ankur (Prabandhan: Indian Journal of Management, 2022)
Report cards not only attest to students’ academic performance in a program, but they also contain several valuable insights. The study was based on the analysis of information readily available on the report cards of MBA Ist semester students. Report cards of 1,301 students enrolled in Dr. APJ Abdul Kalam Technical University, India (Asia’s largest affiliating University) affiliated institutions were examined. The study identified two types of courses: quantitative courses and non-quantitative courses. Furthermore, students’ performance varied significantly between categories, and quantitative courses were more difficult to score than non-quantitative courses. Decision models capable of predicting ‘overall academic performance’ were developed using multiple linear regression analysis. Report cards were used to collect data on the dependent variable (overall academic performance) and five predictor variables (gender, ethnicity, and students’ performance in three quantitative courses, namely managerial economics, business statistics, and business accounting). Finally, the study discovered that the predictor variable ‘AGP in Managerial Economics’ had the most significant impact on overall academic performance. Then came ‘AGP in Business Statistics,’ ‘AGP in Business Accounting,’ and the gender of the students.